The landscape of chromothripsis across adult cancer types - Voronina, Natalia; Wong, John K. L.; Hübschmann, Daniel; Hlevnjak, Mario; Uhrig, Sebastian; Heilig, Christoph E.; Horak, Peter; Kreutzfeldt, Simon; Mock, Andreas; Stenzinger, Albrecht; Hutter, Barbara; Fröhlich, Martina; et al. (Nature Communications, 2020)
Chromothripsis is a recently identified mutational phenomenon, by which a presumably single catastrophic event generates extensive genomic rearrangements of one or a few chromosome(s). Considered as an early event in tumour development, this form of genome instability plays a prominent role in tumour onset. Chromothripsis prevalence might have been underestimated when using low-resolution methods, and pan-cancer studies based on sequencing are rare. Here we analyse chromothripsis in 28 tumour types covering all major adult cancers (634 tumours, 316 whole-genome and 318 whole-exome sequences). We show that chromothripsis affects a substantial proportion of human cancers, with a prevalence of 49% across all cases. Chromothripsis generates entity-specific genomic alterations driving tumour development, including clinically relevant druggable fusions. Chromothripsis is linked with specific telomere patterns and univocal mutational signatures in distinct tumour entities. Longitudinal analysis of chromothriptic patterns in 24 matched tumour pairs reveals insights in the clonal evolution of tumours with chromothripsis.